2013
DOI: 10.1103/physrevlett.110.267202
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Spin-Orbit Enhanced Electric-Field Control of Magnetism in MultiferroicBiFeO3

Abstract: We present a microscopic theory that shows the importance of spin-orbit coupling in perovskite compounds with heavy ions. In BiFeO3 (BFO) the spin-orbit coupling at the bismuth ion sites results in a special kind of magnetic anisotropy that is linear in the applied E field. This interaction can convert the cycloid ground state into a homogeneous antiferromagnet, with a weak ferromagnetic moment whose orientation can be controlled by the E-field direction. Remarkably, the E-field control of magnetism occurs wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 31 publications
3
31
0
Order By: Relevance
“…which agrees with the first ANI-induced polarization proposed by deSousa et al [48]. An additional perpendicular polarization…”
Section: Ani-induced Polarizationssupporting
confidence: 92%
“…which agrees with the first ANI-induced polarization proposed by deSousa et al [48]. An additional perpendicular polarization…”
Section: Ani-induced Polarizationssupporting
confidence: 92%
“…5). This dramatic difference is similar to the difference in T M values of PbFe 1=2 Nb 1=2 O 3 ð …150 K) and its lead-free counterparts A 2þ Fe 1=2 Nb 1=2 O 3 ðA ¼ Ca, Sr, Ba) ( …20 K) 35,36 and seems to be due to additional contribution of the superexchange between Fe 3þ ions via the empty 6p-states of Bi 3þ to the overall superexchange in accordance with predictions of De Sousa et al 38 The absence of the MðTÞ anomaly at around 150 K for 0.5NaNbO 3 -0.5BiFeO 3 composition seems to be due to the strong diffusion of this anomaly. Similar "disappearance" of the MðTÞ anomaly corresponding to antiferromagnetic phase transition was observed, e.g., for some compositions of the PbFe 2=3 W 1=3 O 3 -PbTiO 3 , BiFeO 3 -PbTiO 3 and PbFe 1=2 Nb 1=2 O 3 -PbTiO 3 solid solutions.…”
Section: Resultssupporting
confidence: 88%
“…M€ ossbauer studies have shown that while for 0.5BiFeO 3 -0.5NaNbO 3 the T M value is about 150 K, for 0.5LaFeO 3 -0.5NaNbO 3 it is only …25 K. Similar large difference in T M values is known for lead-containing PbFe 1=2 Nb 1=2 O 3 ð …150 K) and its lead-free counterparts A 2þ Fe 1=2 Nb 1=2 O 3 ðA ¼ Ca, Sr, Ba) ( …20 K) and is ascribed to the magnetic superexchange between Fe 3þ ions via the empty 6p-states of Pb 2þ ions. 35,36 Thus, the results obtained for 0.5BiFeO 3 -0.5NaNbO 3 and 0.5LaFeO 3 -0.5NaNbO 3 seem to be an experimental evidence of the magnetic superexchange between Fe 3þ ions in BiFeO 3 via the empty 6p-states of Bi 3þ ions theoretically predicted by De Sousa et al 38…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…[1][2][3][4][5] As promising oxides, BiAlO 3 and BiGaO 3 are predicted that they should be high performance piezoelectrics and ferroelectrics with large spontaneous polarization from the hypothetical perovskite structure. 6 Experimentally, bulk perovskite-like BiAlO 3 and pyroxene-like BiGaO 3 have been synthesized using a high-pressure and high-temperature technique and their structure parameters were refined.…”
Section: Introductionmentioning
confidence: 99%